Potency of use ferrous sulphate from iron waste workshop bubut for raw material pharmacy - Sunardi Sunardi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
Iron Deficieny Anemia (IDA) representing one of especial micronutrient deficiency that happened in Indonesia. IDA suffered by Indonesia resident about 100 million soul. One of effort of handling IDA is supplementation by ferro sulphate. To serve the purpose of raw material pharmacy have to be up to standard quality of set in Pharmacopoeia of Indonesia Edition IV.This Research aimed to make, to purify and characterization ferro sulphate from iron waste. The produce with reacted iron waste and acid sulphate 25% during 2 day. Crystal dissociated and purified by recrystalization, and then characterization with SEM-EDS.Result of research showed that ferro sulphate from iron waste of workshop bubut fulfill the standard quality of in Indonesia Pharmacopoeia Edition IV.Key words : iron waste, ferrous sulfate, recrystalization, characterization.